Eleven daughters of NANOG. - Booth, H; Holland, P (2004)
Nanog is a recently discovered ANTP class homeobox gene. Mouse Nanog is expressed in the inner cell mass and in embryonic stem cells and has roles in self-renewal and maintenance of pluripotency. Here we describe the location, genomic organization, and relative ages of all human NANOG pseudogenes, comprising ten processed pseudogenes and one tandem duplicate. These are compared to the original, intact human NANOG gene. Eleven is an unusually high number of pseudogenes for a homeobox gene and must reflect expression in the human germ line. A pseudogene orthologous to NANOGP4 was found in chimpanzee and an expressed pseudogene in macaque. Examining pseudogenes of differing ages gives insight into pseudogene decay, which involves an excess of deletion mutations over insertions. The mouse genome has two processed pseudogenes, which are not clear orthologues of the primate pseudogenes.